Studentification, youthification, and gentrification, all at once? New-builds, newcomers, and near-campus change in a post-industrial city - Zasina, Jakub; Jakubiak, Wiktoria (Bulletin of Geography. Socio-economic Series, 2024)
Higher education growth changes the neighbourhoods of university cities in multiple ways. The most evidenced way is studentification, although researchers also report youthification and gentrification. However, empirical studies on near-campus change through the tri-conceptual prism of studentification, youthification, and gentrification are recent and limited to North America. Therefore, we apply it to another context. In this paper, we look at Lodz, Poland, and its campus-adjacent, post-industrial area that is facing a housing boom. We describe the new-builds (their scale, types, and morphologies) and the newcomers (their demographics, residential choices, satisfaction and plans). As a result, we claim the change here is a gentrification-like hybrid of new-build youthification and studentification. Consequently, we suggest that boundaries between studentification, youthification, and gentrification can be fuzzy in particular locales. We also nuance previous findings about the near-campus change, especially the features of studentification and studentifiers, and the role of the campus itself in this process.